2008
DOI: 10.1017/s1751731108002747
|View full text |Cite
|
Sign up to set email alerts
|

Association between PrP genotypes and performance traits in a Welsh Mountain flock

Abstract: The UK national scrapie plan (NSP) for sheep is based on selection for the resistant ARR/ARR genotype and elimination of susceptible types of the ovine prion protein (PrP) gene. The aim of this study was to estimate the possible association of the PrP genotype and performance traits by using data from the CAMDA Welsh Mountain flock. Four alleles (ARH, ARQ, ARR and VRQ) and 10 genotypes covering all five NSP risk groups were present in the CAMDA flock. Overall, the most common allele was ARR (35.2%), and VRQ wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In this breed, the homozygous ARR lambs also had the lowest 8-week weights, the lowest scan weights and consequently the lowest average daily weight gains, although the results for these traits failed to reach the 5% significance threshold. A similar result was reported by Pritchard et al (2008) in the same breed, with homozygous and heterozygous ARR lambs being lighter than non-carriers at scanning. Given that ARR carriers collectively represent more than 85% of the genotyped population, and the direction of the effect is for decreased weights in a commercially relevant trait, the impact on the Welsh Mountain breed may be important.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this breed, the homozygous ARR lambs also had the lowest 8-week weights, the lowest scan weights and consequently the lowest average daily weight gains, although the results for these traits failed to reach the 5% significance threshold. A similar result was reported by Pritchard et al (2008) in the same breed, with homozygous and heterozygous ARR lambs being lighter than non-carriers at scanning. Given that ARR carriers collectively represent more than 85% of the genotyped population, and the direction of the effect is for decreased weights in a commercially relevant trait, the impact on the Welsh Mountain breed may be important.…”
Section: Discussionsupporting
confidence: 86%
“…Alternatively, they have been performed on experimental rather than on commercial sheep populations (Man et al, 2006;Sawalha et al, 2007). Only the study of Pritchard et al (2008) has focused on commercial lamb performance data in a numerically important breed, the Welsh Mountain.…”
Section: Introductionmentioning
confidence: 99%
“…A study on three UK hill breeds by Moore et al (2009), showed that only the Welsh Mountain breed had any associations with ultrasonic traits in which the ARR and AHQ alleles were associated with lower muscle depths, while VRQ carriers were associated with more fat than other genotypes. In the same breed, Pritchard et al (2008) observed a contrasting result in which ARR homozygous lambs had significantly greater muscle depth than ARR heterozygous lambs. Extensive studies failed to show any significance of PrP genotype in determining the depth of muscle or fat in many other European sheep breeds (Roden and Haresign, 2001;Prokopova et al, 2002;de Vries et al, 2004;Vitezica et al, 2005;Isler et al, 2006;Man et al, 2006;Sawalha et al, 2007a;Sweeney and Hanrahan, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…This led to the initiation of a research project in which potential associations between PrP genotype and performance and survival traits were investigated in a variety of sheep breeds from all sectors of the sheep industry in Great Britain. Results for hill breeds have now been reported (Man et al, 2006;Sawalha et al, 2007a;Pritchard et al, 2008;Moore et al, 2009), with the general conclusion being that although significant associations between PrP genotype and lamb performance are occasionally seen, these are generally small in magnitude and not consistent across breeds. However, the majority of British slaughter lambs are sired by terminal sire (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on sheep reported that no association exists between the PRNP and the most relevant economic traits in the sheep industry (reproductive and growth traits; meat traits and milk traits). Therefore, selection for scrapie resistance will not adversely affect progress in the traits (Vitezica et al, 2005(Vitezica et al, and 2013Pritchard et al, 2008).…”
Section: Introductionmentioning
confidence: 99%